Expression of the drug transporters MDR1/ABCB1, MRP1/ABCC1, MRP2/ABCC2, BCRP/ABCG2, and PXR in peripheral blood mononuclear cells and their relationship with the expression in intestine and liver - Albermann, Nadine; Schmitz-Winnenthal, Friedrich Hubertus; Z’graggen, Kaspar; Volk, Christine; Hoffmann, Michael Marcus; Haefeli, Walter E.; Weiß, Johanna (Biochemical pharmacology, 2005)
ATP binding cassette (ABC)-transporters like P-glycoprotein (multidrug resistance (MDR)1/ABCB1), the multidrug resistance associated proteins 1 and 2 (MRP1/ABCC1 and MRP2/ABCC2), and the breast cancer resistance protein (BCRP/ABCG2) have a large impact on the pharmacokinetics of numerous drugs and may also modulate the effectiveness of drug therapy. Prediction of a patient's susceptibility to xenobiotics and individualization of drug therapy would become possible, if a simple test were available for an easy screening of transporter expression. This study quantified the mRNA expression of the four ABC-transporters and of the pregnane X receptor (PXR), a key regulator in drug metabolism and efflux, in peripheral blood mononuclear cells (PBMCs), and corresponding liver or small intestine samples of humans by real-time reverse transcription-polymerase chain reaction (RT-PCR). The results obtained prove the absence of a correlation between the expression of four major ABC-transporters in PBMCs and in the intestine or liver. For all transporters (except MRP1/ABCC1 in the intestine), mRNA amount of the ABC-transporters was positively correlated with PXR expression in PBMCs and intestine. In conclusion, the study suggests that basal expression levels of the transporters are directly influenced by PXR expression in liver and PBMCs and demonstrates that PBMCs do not qualify as surrogate tissue for the expression of the four ABC-transporters in small intestine and liver. However, the transporter status in PBMCs remains important for drugs, whose primary site of therapeutic action is the lymphocyte and which are known substrates of the transporters.
Gesehen am 18.05.2021